The effect of adipose tissue on transdermal monochromatic light presented to the human fetus using Monte Carlo simulations - Zac Isaac; Jacob Heerikhuisen; Vincent Reid (Scientific Reports)
Abstract The extent to which transdermal light sources illuminate the uterine environment is unknown. Recent work indicates the human fetus responds to external visual stimuli, such as laser diodes, and initial modeling suggests the fetus may not develop in a completely dark environment as previously assumed. Development of the human visual system begins within the womb, and there is motivation in fields such as developmental psychology, transabdominal oximetry, and photoacoustics to explore the extent to which light penetrates maternal abdominal tissue and understand how transdermal stimuli appear to the fetus. We develop and adapt a Monte Carlo model utilising third trimester histological properties of maternal tissue to simulate transdermal monochromatic collimated light sources, with particular focus on the 650 nm wavelength used in experimental applications. We determine approximate levels of third trimester uterine illumination from such stimuli, ranging from being comparable to an overcast night to a full moon in clear conditions. We further discuss the scope for multiple stimuli to be visibly distinct in utero for experimental applications. This modeling provides quantitative guidance on the interactions between transdermal monochromatic collimated source laser diode stimuli and maternal tissue to practitioners and researchers in the fields of fetal vision, ultrasound, and developmental psychology.